Conversion of depolymerized sugars and aromatics from engineered feedstocks by two oleaginous red yeasts. (August 2019) - Rodriguez, Alberto; Ersig, Nadine; Geiselman, Gina M.; Seibel, Katharina; Simmons, Blake A.; Magnuson, Jon K.; Eudes, Aymerick; Gladden, John M.
Highlights: Hydrolysates obtained with different pretreatments are compatible with red yeasts. Biomass from engineered Arabidopsis lines yielded aromatics that can be assimilated. Bisabolene-producing red yeast species were engineered and characterized. Abstract: One of the requirements for efficient biological conversion of lignocellulose to bioproducts is the compatibility of biological catalysts with the processes employed to solubilize and depolymerize the lignocellulosic components. The red yeasts Rhodosporidium toruloides and Rhodotorula mucilaginosa were evaluated for their ability to assimilate sugars and aromatic compounds extracted from two engineered lines of Arabidopsis thaliana with modified lignin or the wild-type using ionic liquid, acid or alkaline pretreatments. Differential amounts of monomeric sugars, organic acids and, in the case of the engineered lines, either 4-hydroxybenzoic or protocatechuic acid were additionally released from the biomass and found to be tolerated and consumed by both microorganisms. Genetically-engineered strains of the two red yeasts successfully converted the depolymerized products into the biofuel precursor bisabolene when cultivated on hydrolysates or synthetic media containing specific sugars, acids and aromatics found in the hydrolysates.